Functions, Standardizations, and Humanity Management: An Inventory Study of Chinese Green Food Culture and Industry - Tian , Xia; Tian, Robert Guang (Journal of Ecohumanism, 2025)
Through an in-depth exploration of knowledge of Chinese green food culture and industry, this paper attempts to offer insight into the functions, standardizations, and humanity management in contemporary China’s time-honored catering enterprises. It employs a vertical and horizontal study methodology to demonstrate the panoramic history and perceptional present. The study finds out that the popular way to enhance functions, standardizations, and humanity management in Chinese catering enterprises is to spread the knowledge of Chinese green food culture and industry so that Chinese cuisine could better associate past, present, and future, as well as self and others, addressing the predicament of food, culture, industry, and its sustainability. Food cultural knowledge can broaden the visions of humanity management studies and enlighten scholars vertically and horizontally. Integrating food culture and humanity management will boost the spread of Chinese green food culture and redound to Chinese catering enterprises’ functions, standardizations, and humanity management. The knowledge of Chinese green food culture and industry demonstrates its inheritance situation among some China Time-Honored restaurants, standardization production of food and its life-nourishing function in the catering industry studies on one hand. This paper is a tentative exploration to expound the understanding of Chinese green food culture and industry and its contribution to catering enterprises in humanity management studies, such as product design, staff management, and entrepreneurship in the Chinese context.